Experimental study of the POP technique: focus on the physical basis of the process. Issue 6 (November 2020) - Royon, Laurent; Merckx, Jacques; Herbaut, Rémi; Brunet, Philippe; Dupont, Christian; Dantan, Philippe; Flaud, Patrice; Guiffant, Gérard
Introduction: Central or peripheral vascular access devices have been in use for many decades. However, despite adequate care and maintenance, complete occlusion may occur, and its impact cannot be overlooked. A new procedure using a percussion technique has been published and referred as 'the POP technique'. Methods: A hydrodynamic bench was used permitting both the recording of the movement of the piston with a fast camera and the pressure variations in the polyurethane and silicone catheters while connected to 2- and 3-piece syringes. Results: The results are twofold. First the upward movement of the piston leads to the installation of a saturation vapour pressure in the body of the syringe. During this sequence, the clot is submitted to a force of aspiration. Then the release of the plunger leads to a pulse pressure whose dynamics and intensity are dependent of the types of syringes and catheters. Conclusions: The experiments bring to light the importance of practical features such as the orientation of the syringe and the nature of the polyurethane or silicone catheters. Then the analysis enables the definition of practical rules for safe practice of the POP technique. This study will impact clinicians as many may be tempted to use the technique in hope to resolve the occlusion safely, in a timely manner.